2012
DOI: 10.1111/j.1463-1318.2012.03079.x
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide study on anastomotic leakage after colonic cancer surgery

Abstract: The main finding that a laparoscopic approach was associated with an increased risk of AL should prompt close future monitoring. There was no evidence that centralization of surgery to high-volume hospitals reduced the rate of AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
111
12
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 28 publications
10
111
12
8
Order By: Relevance
“…Despite the small sample size, our rate was not high in reference to previous reports. [17,18] Regarding previous report, our SSI rate was higher, but small sample size of our study makes it difficult to explain this results. [19,20] It should be noted that we did not experience any conversion to open surgery.…”
Section: Discussioncontrasting
confidence: 51%
“…Despite the small sample size, our rate was not high in reference to previous reports. [17,18] Regarding previous report, our SSI rate was higher, but small sample size of our study makes it difficult to explain this results. [19,20] It should be noted that we did not experience any conversion to open surgery.…”
Section: Discussioncontrasting
confidence: 51%
“…Some studies have identified laparoscopic surgery as a risk factor for anastomotic leakage [14] whereas others have not found any association between the approach and the incidence of anastomotic leakage [23,24]. In this study, incidence of anastomotic leakage was slightly higher in open surgery than in laparoscopic surgery though it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 47%
“…Men, because of the narrow pelvis, offer greater challenge during pelvic dissection, and hence increased risk of anastomotic leakage [14]. In this study, incidence of anastomotic leakage was slightly higher in men than in women though it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 48%
“…Anastomotic leakage is the most feared and potentially fatal complication after colorectal surgery because usually results in high morbidity and mortality, increase length of stay, medical costs and is associated with poorer long-term oncological results [1][2][3][4][5] . The prevalence of anastomotic leakage has been reported to range from 1 to 26% 1,2,[6][7][8][9][10][11] . Multiple factors are involved in healing process of colorectal anastomosis, including technical-related factors and patients-specific characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%